The Effect of Managerial Ownership and Company Size on Firm value with Capital Structure as Moderating Variables in Manufacturing Companies Listed in Indonesia Stock Exchange 2016-2018 - Asmaul Husna (Kusuma Negara Business School, 2020)
This research aims to find out the effects of managerial ownership and companies sizes on the companies values using capital structure as the moderating variable. The population in this study is all manufacturing companies registered on Indonesian Stock Exchange (BEI) from 2016-2018. This research’s sample was conducted by purposive sampling, with 22 total samples obtained. The type of data used was a secondary data gained from www.idx.co.id. The data obtained was then analyzed using Multiple Linier Regression with 2.2 version of SPSS Program. The results revealed that 1). According to the result of the test using multiple regression and hypothesis test with partial test (t-test) demonstrated that managerial ownership variable has positive and significant effects on manufacturing companies values registered on BEI in 2016-2018. 2). Based on the test result using multiple regression and hypothesis test with partial test (t-test) showed that the companies sizes bring positive and significant impacts on manufacturing companies values registered on BEI in 2016-2018. 3). According to the test result using multiple regression and hypothesis test with partial test (t-test) described that capital structure variable gives negative and significant impacts on manufacturing companies values registered on BEI in 2016-2018. 4). According to the result of the test using moderating regression, it was emphasized that capital structure variable has the capability to moderate the relationship between managerial ownership on manufacturing companies values registered on BEI in 2016-2018. 5). Based on the result of the test using moderating regression, it was discovered that capital structure variable is able to moderate the relationship between a company’s sizes on manufacturing companies’ values registered on BEI in 2016-2018.